CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI PENGARUH MANAJEMEN LABA DAN AKTIVITAS RIIL TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Budiana, Desak Made Prami Utari; Suputra, I D.G Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to provide empirical evidence about corporate social responsibility as a moderating influence earning management and real activity on stock return. This study uses an external secondary data which is obtained by researchers indirectly through and intermediary, sach as other people or documents. The population is the study using 410 manufacturing companies with the observation in 2010 until 2014. Sample selection technique is using purposive sampling and there are 182 observations sample obtained and testing tools used is the analysis Moderated Regression Analysis (MRA). This first research results prove that earnings management by discretionary accrual proxy has no effect on stock returns, the results of the second study showed that the activity of the real proxied by the cash flow from operating activities impact on stock return. The results of a third study corporate social responsibility weaken earnings management influence on stock returns, while the fourth research results prove that corporate social responsibility strengthens the influence of real activity on stock return.
Keywords: Corporate Social Responsibility, Profit Management, Real Activity and Stock Returns